An introduction to XML and Web technologies - Møller, Anders (Addison-Wesley, 2006)
Divided into two parts, this book describes the technical features of each standard of web technologies, compares closely related technologies and shows how to implement them in various application scenarios. It is for students on web development or XML courses, and for practitioners seeking to improve their insight into this subject area.